Efficacy and safety of manufactured Chinese herbal formula for cervical radiculopathy: protocol for a systematic review with meta-analysis and trial sequential analysis - Bao, Xiaohang; Huang, Baohua; Li, Canmei; Gan, Weixiong; Li, Zhifei; Xu, Wei; Zhang, Yisheng; Tang, Bin (Frontiers in Neurology, 2025)
BackgroundManufactured Chinese herbal formulas (MCHFs) are Chinese patent medicine preparations made from a variety of herbal ingredients. These formulas are processed into specific dosage forms in accordance with defined prescriptions and manufacturing procedures, and are intended for the prevention and treatment of various diseases. As a type of commercialized Chinese patent medicine, MCHFs are listed and marketed in China upon approval by the National Medical Products Administration (NMPA). MCHFs can be used to treat cervical radiculopathy (CR) and alleviate its symptoms, but the efficacy of MCHFs compared to conventional oral drugs for the treatment of CR has not been thoroughly explored. Therefore, this meta-analysis aimed to assess and compare the efficacy of MCHF with that of conventional oral drugs for the treatment of CR.MethodsThe meta-analysis was conducted following the guidelines outlined in the Cochrane Handbook and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) checklist. A comprehensive search was conducted in PubMed, the Excerpta Medica database (EMBASE), the Cochrane Central Register of Controlled Trials (CENTRAL), and three Chinese electronic databases, including the National Knowledge Infrastructure (CNKI), Wanfang Digital Periodicals (WANFANG), and the Chinese Science and Technology Periodicals (VIP) database. We limited the type of literature included to RCT, and there was no language restriction. Two independent reviewers used the NoteExpress tool to screen studies, extract data, and assess the quality of the studies. The global Visual Analog Scale (VAS) pain score measured at the end of the treatment period was the primary outcome. Secondary outcomes included the Neck Disability Index (NDI), the Japanese Orthopedic Association (JOA) score, the 36-Item Short Form Health Survey (SF-36) score, and adverse events. If feasible, a meta-analysis was conducted in Review Manager 5.4; otherwise, a descriptive analysis was performed. The grading of recommendations assessment, development, and evaluation (GRADE) approach was used to assess the evidence level of the meta-analysis for primary outcome measure and all secondary outcome measures, and trial sequential analysis (TSA) was performed for the primary outcome measure.DiscussionThis predefined protocol is intended to enhance transparency, avoid future duplication of efforts, and generate reliable evidence regarding the efficacy and safety of MCHF in the treatment of cervical radiculopathy.